THE DEVELOPMENT AND USE OF SHOPPING LISTS IN GROCERY SHOPPING IN SWEDEN - Berndt, Adele; Angstmann, Kim; Strauch, Anna-Katharina (Advances in Social Sciences Research Journal, 2017)
Shopping lists are developed prior to a shopping trip and used in-store, making them part of pre-shopping and in-store behaviour. The purpose of the research was to investigate various factors such as store knowledge and list design that can impact their development and use. A descriptive study was executed gathering shopping lists, till receipts and a response sheet from customers over a period of one week. The findings show customers are most likely to write product categories on the lists, compiled using scraps of paper. Lists were compiled using the store leaflet but consumers did not rely on their store knowledge in its development. Further, the majority of respondents deviated from their prepared list, resulting in incomplete or unplanned purchases.The small sample as well as the location can be viewed as limitations in the study. Understanding the way in which these lists are developed can assist retailers in their marketing both prior to the shopping trip and in-store. Retailers can gain a better understanding of the planning and use of lists seek ways to influence this process. This study provides detail on how lists are compiled by consumers while also suggesting the importance of in-store cues as the majority of customers are open to deviating from the list.